2023
DOI: 10.1038/s41392-023-01406-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of the gut microbiota in anticancer therapy: from molecular mechanisms to clinical applications

Abstract: In the past period, due to the rapid development of next-generation sequencing technology, accumulating evidence has clarified the complex role of the human microbiota in the development of cancer and the therapeutic response. More importantly, available evidence seems to indicate that modulating the composition of the gut microbiota to improve the efficacy of anti-cancer drugs may be feasible. However, intricate complexities exist, and a deep and comprehensive understanding of how the human microbiota interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 426 publications
0
20
0
Order By: Relevance
“…CRC is characterized by a highly inflammatory environment and disruption of the intestinal barrier, which may facilitate the entry of certain microorganisms and promote the colonization of other microorganisms within the tumor. Various factors can lead to the breakdown of the mucosal barrier, allowing microorganisms to infiltrate the tumor ( 50 ). In this study, the recruitment of SAM to the CRC environment allowed the microrobots to successfully reach the cancer site.…”
Section: Resultsmentioning
confidence: 99%
“…CRC is characterized by a highly inflammatory environment and disruption of the intestinal barrier, which may facilitate the entry of certain microorganisms and promote the colonization of other microorganisms within the tumor. Various factors can lead to the breakdown of the mucosal barrier, allowing microorganisms to infiltrate the tumor ( 50 ). In this study, the recruitment of SAM to the CRC environment allowed the microrobots to successfully reach the cancer site.…”
Section: Resultsmentioning
confidence: 99%
“…type III secretion system (T3SS) of Salmonella enterica can bind the effector protein AvrA and cyclomodulin‐like protein typhoid toxin, promoting tumorigenesis genetically and epigenetically, through genotoxin‐mediated mutagenesis [365]. Specifically, AvrA promotes cell proliferation and differentiation and inhibits cell cycle arrest via the JAK/STAT, Wnt/ β‐catenin or acetyltransferase‐targeted p53 pathway, collectively resulting in tumorigenesis [366, 367]. To sum up, cancer‐promoting bacteria may participate in the process of oncogenesis through a variety of different molecular pathways, and several main mechanisms are summarized here (Figure 8).…”
Section: Cell‐autonomous and Non‐autonomous Emerging Functions Of P53...mentioning
confidence: 99%
“…Studies have shown that the gut microbiota can modulate cancer treatments' efficacy and adverse effects, and that cancer and anticancer therapies interact bidirectionally with the gut microbiota 134 . In addition, certain gut microbes have been found to protect against inappropriate inflammation and modulate the immune response, which is particularly relevant to breast cancer immunotherapy 135 . Clinical and preclinical studies have demonstrated that the gut microbiota strongly influences tumor response to immune checkpoint blockade, with follow‐up studies showing an enhancement of the T cell response via the activation of antigen presenting cells, such as dendritic cells, in mice models with a stable healthy gut microbiome 89,136 .…”
Section: Technological Advances In Breast/gut Microbiome Research: a ...mentioning
confidence: 99%